Ict Literacies of Teachers in the Division of Northern Samar: A Meta-Analysis - Corrige, Liezel Francisco (PT. Antis International Publisher, 2024)
This meta-analysis on ICT literacies of the teachers in the Division of Northern Samar was based on the studies available in the UEP-Graduate Studies for over a five-year period. It looked into the profile of the teachers in terms of age, sex, ICT-related trainings, and personal ICT devices. This study also determined the level of ICT literacies of teachers in terms of ICT competence, extent of ICT integration, and level of ICT utilization. Studies showed that smartphone was the most common ICT device of the respondents and this was also what they preferred using as an aid in their teaching. It was also recorded that the respondents also owned laptops and desktop computers that they used in the teaching-learning process. Most of the respondents of the studies were only at the average level when it comes to ICT competence, except for the findings of Diaz (2016) where the respondents were only at the basic level, and the study of Virtudes (2018) who found out that the respondents were already at the advance level. This can be attributed to the lack of ICT-related trainings. In terms of the extent of ICT integration, results revealed that the teachers were already knowledgeable enough of the capabilities of computers to classroom applications, but were not proficient enough using computers to support the teaching-learning process. Even if the respondents had knowledge in using ICT, they were not maximizing these technologies in the teaching-learning process. Others were not comfortable in using ICT because they were still not experts, and most of them had only an average literacy on ICT. They still wanted to use strategies which they were comfortable with, and ICT was out of the context. Results confirm that teachers are mostly using ICT only as aids in generating electronic reports, record of students’ data and files, acquiring teaching materials through the internet, and improving their classroom. But although they can be considered literate enough to the use of ICT, they are not fully utilizing ICT into the teaching-learning process.